Aerobiological study in Lima, Peru - Silvia Uriarte; Óscar Calderón (Revista Alergia México, 2018)
Background: Knowledge about seasonal and annual fluctuations in airborne pollen and fungal spores in any geographical area is essential for effective diagnosis and treatment of allergy diseases.